The Impact of Green Human Resource Management Practices on Employee Well-being and Job Satisfaction - Rasmussen, Vienna Anggraeni; Hermawan, Rian; Lucky, Nathaniel Putra; Prasetyaningtyas, Sekar Wulan (Yayasan Sinergi Kawula Muda, 2024)
This study delves into the positive impact of Green Human Resource Management practices on job satisfaction and employee well-being within Indonesian companies, with a specific focus on the real estate development sector. As part of a burgeoning global movement towards environmental consciousness, Indonesian businesses are increasingly embracing eco-friendly practices to bolster their competitive edge, cultivate an environmentally responsible image, and attract employees who prioritise sustainability. The research meticulously examines the efficacy of distinct GHRM practices, such as environmental training and decision-making involvement, in nurturing employee well-being and job satisfaction. The methodology employs a quantitative approach, utilising online surveys distributed to top Indonesian property development company employees. The analysis unequivocally confirms that GHRM practices significantly enhance employee well-being and job satisfaction, with employee well-being serving as a mediator that amplifies the positive effect of GHRM on job satisfaction. The findings underscore the pivotal role of comprehensive GHRM strategies in fostering a supportive and sustainable work environment, thereby contributing to overall organisational success. This study enriches the literature on sustainable human resource management, underscoring the imperative for companies to implement GHRM practices to bolster employee well-being and job satisfaction, and convincing the audience of the commitment needed for this transformative process.